2022
DOI: 10.36740/wlek202206112
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Morphoetiopathogenesis of Acute Appendicitis and Consequences After Appendectomy

Abstract: The aim: To study the features of morphoethiopathogenesis of acute appendicitis and the consequences after appendectomy. Materials and methods: 10 preparations of human appendix were studied, from which 5 appendixes were normal in people who died in adulthood and old age and 5 processes were taken intraoperatively during appendectomy. Morphometric characteristics of the tissue structures of the preparations were compared with the systematic review data, the literature search by the following keywords: morphoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…However, the data presented in our publication on the consolidation of the greater omentum and serous formations of the epididymides, completely homologous to the latter (Hryn et al, 2022;Hryn et al, 2023b), with the perforated openings of the cecum have not been found in the scientific literature, as well as the morphological aspects of the local immune response to infection of the peritoneal cavity of the experimental animals.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, the data presented in our publication on the consolidation of the greater omentum and serous formations of the epididymides, completely homologous to the latter (Hryn et al, 2022;Hryn et al, 2023b), with the perforated openings of the cecum have not been found in the scientific literature, as well as the morphological aspects of the local immune response to infection of the peritoneal cavity of the experimental animals.…”
Section: Discussionmentioning
confidence: 67%
“…Currently, in experimental medicine, many different methods of modeling septic peritonitis are known (Sydorchuk, 2015;Vintrych et al, 2022;Brown et al, 2023). At the same time, in each case, the experiment should consider the optimal assessment of known etiological factors in its pathogenesis, among which the most common cases are ulcerative perforation of the stomach or duodenum, as well as perforation of the cecal appendage in its gangrenous inflammation (Hryn et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Тому Yildirim A. (2010) і Hryn V. (2022) вважають подібні лімфоїдні скупчення імунними фабриками черевної порожнини [9,13]. Незважаючи на те, що ще в 1921 році вчені наголошували на наявності молочних плям у в черевній порожнині та їх велике біологічне значення, результатів експериментальних досліджень, пов'язаних з молочними плямами все ще залишається відносно мало.…”
Section: вступunclassified
“…Проблема перитоніту на сьогодні вивчена досить широко [11,[33][34][35]. Перитоніт є ускладненням, а точніше -неминучим наслідком або етапом розвитку різних гострих хірургічних захворювань і травм органів черевної порожнини.…”
Section: роль великого чепця при перитонітіunclassified